Bedload transport measurements with impact plate geophones: comparison of sensor calibration in different gravel‐bed streams. Issue 7 (2nd December 2013) - Rickenmann, Dieter; Turowski, Jens M.; Fritschi, Bruno; Wyss, Carlos; Laronne, Jonathan; Barzilai, Ronel; Reid, Ian; Kreisler, Andrea; Aigner, Johann; Seitz, Hugo; Habersack, Helmut
ABSTRACT Indirect bedload transport measurements have been made with the Swiss plate geophone system in five gravel‐bed mountain streams. These geophone sensors record the motion of bedload particles transported over a steel plate mounted flush with the channel bed. To calibrate the geophone system, direct bedload transport measurements were undertaken simultaneously. At the Erlenbach in Switzerland, a moving‐basket sampler was used. At the Fischbach and Ruetz streams in Austria, a Helley–Smith type bedload sampler provided the calibration measurements. A Bunte‐type bedload trap was used at the Rofenache stream in Austria. At the Nahal Eshtemoa in Israel, Reid‐type slot bedload samplers were used. To characterize the response of the geophone signal to bedload particles impacting on the plate, geophone summary values were calculated from the raw signal and stored at one second intervals. The number of impulses, i.e. the number of peaks above a pre‐defined threshold value of the geophone output signal, correlated well with field measured gravel transport loads and was found to be a robust parameter. The relations of impulses to gravel transport loads were generally near‐linear, but the steepness of the calibration relations differed from site to site. By comparing the calibration measurements from the different field sites and utilizing insights gained during preliminary flume experiments, it has been possible to identify the main factors that are responsible for site specific differences in the calibration coefficient. The analysis of these calibration measurements indicates that the geophone signal also contains some information about the grain size distribution of bedload. Copyright © 2013 John Wiley & Sons, Ltd.